2017
DOI: 10.1371/journal.pone.0176676
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac glycoside ouabain activates NLRP3 inflammasomes and promotes cardiac inflammation and dysfunction

Abstract: Cardiac glycosides such as digoxin are Na+/K+-ATPase inhibitors that are widely used for the treatment of chronic heart failure and cardiac arrhythmias; however, recent epidemiological studies have suggested a relationship between digoxin treatment and increased mortality. We previously showed that nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasomes, which regulate caspase-1-dependent interleukin (IL)-1β release, mediate the sterile cardiovascular infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
(52 reference statements)
1
26
1
1
Order By: Relevance
“…Interestingly, ouabain enhances interleukin-10 levels in human monocytes (Teixeira and Rumjanek, 2014 ). Recently, Kobayashi et al ( 2017 ) demonstrated that ouabain effect on IL-1β release, in both macrophages and cardiac tissue, is related to NLRP3 inflammasome activation, which in turn is mediated through K + efflux. It is noteworthy that in this study the authors used high doses of ouabain both in vitro and in vivo .…”
Section: Ouabain As a Modulator Of Inflammationmentioning
confidence: 99%
“…Interestingly, ouabain enhances interleukin-10 levels in human monocytes (Teixeira and Rumjanek, 2014 ). Recently, Kobayashi et al ( 2017 ) demonstrated that ouabain effect on IL-1β release, in both macrophages and cardiac tissue, is related to NLRP3 inflammasome activation, which in turn is mediated through K + efflux. It is noteworthy that in this study the authors used high doses of ouabain both in vitro and in vivo .…”
Section: Ouabain As a Modulator Of Inflammationmentioning
confidence: 99%
“…suis , an nlrp3 -deficient human acute monocytic leukemia THP-1 cell line (THP-1- nlrp3 -/- ) and a control cell line (THP-1- nlrp3 +/+ ) were constructed using clustered regularly interspaced short palindromic repeats (CRISPR) technology. Similar to cardiac glycosides ouabain, which activates the NLRP3 inflammasome [31], SC-19 infection induced cleavage of pro-casp1 and pro-IL-1β and secretion of IL-1β in THP-1- nlrp3 +/+ cells, but the activation was significantly inhibited in nlrp3 -/- cells (Fig 2B) . This study was also performed using the murine macrophage cell line J774a.1 with nlrp3 gene knockout (J774a.1- nlrp3 -/- ) and the control cell line J774a.1- nlrp3 +/+ (S2 Fig) .…”
Section: Resultsmentioning
confidence: 85%
“…Transthoracic echocardiography was performed using a digital ultrasound system (Vevo2100 imaging System, Visual Sonics, Toronto, Canada), as previously described 9 , 34 . Briefly, after anesthetization by inhalation of 1.5% isoflurane, two-dimensional targeted M-mode echocardiograms were obtained along the short axis of the LV at the level of the papillary muscles, and at least three consecutive beats were evaluated.…”
Section: Methodsmentioning
confidence: 99%